Life and activity of engineer L.S. Lebedyanski - V. A. Yanin (History of science and technology, 2016)
The following article describes the main aspects of life and activity of engineer L.S. Lebedyanski. It reviews the major working lines and career growing of L.S. Lebedyanski at the Kolomensky plant. In addition, article reviews the contribution of L.S. Lebedyanski to the development of the locomotive industry of the former Soviet Union and his relations with the government.